ArtinM offers new perspectives in the development of antifungal therapy - Ruas, Luciana P.; Carvalho, Fernanda C.; Roque Barreira, Maria Cristina (Frontiers in Microbiology, 2012)
The thermally dimorphic fungus Paracoccidioides brasiliensis is the causative agent of paracoccidioidomycosis (PCM), the most frequent systemic mycosis that affects the rural populations in Latin America. Despite significant developments in antifungal chemotherapy, its efficacy remains limited since drug therapy is prolonged and associated with toxic side effects and relapses. In response to these challenges, it is now recognized that several aspects of antifungal immunity can be modulated to better deal with fungal infections. A common idea for halting fungal infections has been the need to activate a cell-based, pro-inflammatory Th1 immune response to improve the fungal elimination. ArtinM, a D-mannose binding lectin from Artocarpus heterophyllus, has the property of modulating immunity against several intracellular pathogens. Here, we review the immunomodulatory activity of ArtinM during experimental PCM in mice. Both prophylactic and therapeutic protocols of ArtinM administration promotes a Th1 immune response balanced by IL-10, which outstandingly reduces the fungal load in organs of the treated mice while maintaining a controlled inflammation at the site of infection. A carbohydrate recognition based interaction of ArtinM